Report on visit to Malawi, June/July 1976 - Campbell, Bruce M. (1979)
Assessments report on livestock management systems in Malawi. The traditional grazing system, stall-feeder schemes, feedlot systems, milk and dairy produce in Malawi are described with recommendations on possible means of increasing production output.